PENGARUH MARKET ORIENTATION, INOVASI PRODUK, DAN KUALITAS PRODUK TERHADAP KINERJA BISNIS DALAM MENCIPTAKAN KEUNGGULAN BERSAING - Tulus Haryono; Sabar Marniyati (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
The research shown : (1) market orientation direct effect positive and significant to competitive adventage on CV Multi Global Agrindo. (2) market orientation indirect effect positive but not significant to competitive adventage on CV Multi Global Agrindo by business performance. (3) Product inovation direct effect positive and significant to competitive adventage on CV Multi Global Agrindo. (4) Product inovation indirect effect positive and significant to competitive adventage on CV Multi Global Agrindo by business performance. (5) product quality direct effect positive and significant to competitive adventage on CV Multi Global Agrindo. (6) product quality indirect effect positive and significant to competitive adventage on CV Multi Global Agrindo by business performance. (7) business performance is direct effect positive and significant to competitive adventage on CV Multi Global Agrindo.